Dampak Perusakan Antropogenik Terhadap Sedimentasi dan Erosi Pada Hutan Lindung Wosi Rendani Di Kabupaten Manokwari - Mahmud (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2023)
Communities who live around the forest in supporting their daily lives cannot be separated from interactions with the forest, including protected forests impact that triggers erosion, sedimentation, flooding and landslides. This study aims to identify the anthropogenic destruction in Protected Forest of Wosi Rendani (PFWR) and its impact on sediment and erosion. The research was conducted through surveys and data analysis by scoring. The head of the KPHL, forest rangers and retired Forestry Service employees were selected in a purposive sampling. The results showed that anthropogenic activities in the PFWR area included forest encroachment, illegal logging, shifting cultivation by burning, soil extraction and C excavation, conversion to built-up areas. Anthropogenic activities have an impact on increasing sediment from high to very high and erosion in the very high category. The increase in sediment and erosion caused by shrinkage and destruction of PFWR is now remaining 26% which if not managed properly will trigger floods and flash floods.